Anode containing lithium-lanthanum alloy and lithium-ion secondary battery containing same

By using lithium-yttrium alloy negative electrode in lithium sulfur batteries, the problems of lithium branch growth and battery stability are solved, and longer life and higher charge and discharge efficiency are achieved.

JP2025511453AActive Publication Date: 2025-04-16LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024550270
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-30
Filing Date
2023-08-31
Publication Date
2025-04-16
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

In existing lithium-sulfur batteries, lithium metal negative electrodes are prone to react with the electrolyte to form an unstable solid electrolyte boundary layer, resulting in lithium branch growth, internal short circuits and reduced battery capacity and cycle life.

Method used

The lithium-yttrium alloy negative electrode is used to form a stable lithium-yttrium alloy negative electrode by adding yttrium to the lithium alloy, avoiding the growth of lithium branches and improving the cycle stability of the battery.

Benefits of technology

It improves the life and charge and discharge efficiency of lithium sulfur batteries, inhibits the growth of lithium branches, and enhances the mechanical strength and chemical stability of the negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511453000001_ABST
    Figure 2025511453000001_ABST
Patent Text Reader

Abstract

The negative electrode includes a lithium-lanthanum alloy, and the negative electrode can be used as a negative electrode for a lithium-sulfur battery. The lithium-sulfur battery using the alloy negative electrode as described above has improved life characteristics and electrochemical efficiency. In addition, when the lithium-lanthanum alloy is used as the negative electrode, uniform electrochemical plating / elution of lithium is induced, thereby effectively suppressing decomposition of LiPS and lithium salt due to interfacial side reactions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium-sulfur battery having improved battery performance, such as output and capacity.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0110400 filed on August 31, 2022, Korean Patent Application No. 10-2023-0086742 filed on July 4, 2023, and Korean Patent Application No. 10-2023-0114839 filed on August 30, 2023, and the contents disclosed in the specification and drawings of said applications are incorporated herein in their entirety. [Background technology]

[0003] As the range of applications for lithium secondary batteries expands beyond portable electronic devices to include electric vehicles (EVs) and energy storage systems (ESS), the demand for high-capacity, high-energy density, and long-life lithium secondary batteries is increasing.

[0004] Among the various lithium secondary batteries, the lithium-sulfur battery is a battery system that uses a sulfur compound containing a sulfur-sulfur (SS) bond as the positive electrode active material and lithium metal, a carbon-based material capable of intercalating / deintercalating lithium ions, silicon or tin that forms an alloy with lithium metal, etc. as the negative electrode active material.

[0005] Lithium-sulfur batteries have the advantage that sulfur, the main positive electrode active material, has a low atomic weight, is abundant in resources, is inexpensive, non-toxic, and environmentally friendly.

[0006] In addition, lithium-sulfur batteries use a conversion reaction between lithium ions and sulfur at the positive electrode (S8+16Li + +16e -The theoretical specific capacity of the lithium-sulfur battery is 1,675mAh / g, derived from lithium ion battery (Li2S) and 2,600Wh / kg when lithium metal is used as the anode. The theoretical energy density of the lithium-sulfur battery is much higher than that of other battery systems (Ni-MH battery: 450Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO2 battery: 1,000Wh / kg, Na-S battery: 800Wh / kg, lithium-ion battery: 250Wh / kg), and the lithium-sulfur battery has attracted attention among the secondary batteries developed so far due to its high capacity, environmental friendliness, and low price.

[0007] In addition, in the case of lithium-sulfur batteries, when lithium metal is used as the negative electrode active material, the theoretical specific capacity is very high at 3,860mAh / g, and the standard hydrogen electrode (SHE) is also very low at -3.045V, making it possible to realize a battery with high capacity and high energy density. Therefore, research on lithium-sulfur batteries as a next-generation battery system is being actively conducted.

[0008] However, lithium metal, which is an anode active material, has high chemical / electrochemical reactivity and easily reacts with electrolyte, so a protective film called a solid electrolyte interface layer (SEI) is formed on the surface of the anode. The solid electrolyte interface layer formed in this way can suppress direct reaction between the electrolyte and lithium metal and ensure a certain level of stability for anode active materials containing lithium metal, so attempts have been made to form such an SEI layer stably and uniformly on the surface of lithium metal.

[0009] However, in the case of lithium-sulfur batteries, when the negative electrode active material is lithium metal, even if an SEI layer is formed as described above, it is difficult to maintain the SEI layer constant because the electrochemical reaction of the battery continues to occur on the surface of the lithium metal. In addition, the SEI layer formed by the reaction between the electrolyte and lithium metal has a weak mechanical strength, so as the battery is charged and discharged, its structure collapses, causing a local current density difference and forming lithium dendrites on the surface of the lithium metal. In addition, the lithium dendrites thus formed not only increase the physical and chemical instability of the lithium secondary battery by inducing an internal short circuit and inactive lithium (dead lithium) in the battery, but also reduce the battery capacity and cycle life. In addition, the positive electrode active material is dissolved in the form of lithium polysulfide (LiPS) and migrates to the negative electrode to form lithium sulfide by-products, which may cause loss of the positive electrode active material / passivation of the negative electrode and undesired side reactions.

[0010] Due to the high instability of lithium metal and the problem of lithium dendrite formation, various attempts have been made to solve these problems.

[0011] For example, Patent Document 1 discloses that the loss of electrolyte and the formation of dendrites can be prevented by forming a protective layer made of a polymer matrix that can accumulate an electrolyte while protecting the negative electrode on the surface of a negative electrode active material layer containing lithium metal and a lithium alloy.

[0012] Patent Document 2 discloses that the stability and life characteristics of a lithium secondary battery can be improved by suppressing the growth of lithium dendrites by introducing an absorbent material for lithium dendrites into a polymer protective film formed on the surface of lithium metal.

[0013] Although the prior art has been able to suppress the reaction between the electrolyte and lithium metal or the formation of lithium dendrites to some extent, the effect is not sufficient, and there is a problem of deterioration such as hardening or swelling of the protective layer as the battery is charged and discharged.

[0014] Therefore, in the present invention, the lithium-lanthanum alloy negative electrode is directly used as the negative electrode for a lithium-sulfur battery, thereby stabilizing the negative electrode plating / dissolution and improving the cell efficiency and lifespan. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] Korean Patent Publication No. 2016-0034183 [Patent Document 2] Korean Patent Publication No. 2016-0052351 Summary of the Invention [Problem to be solved by the invention]

[0016] The present invention has been made in consideration of the above problems, and has an object to provide a lithium secondary battery with an improved life.

[0017] Another object of the present invention is to provide a negative electrode in which deposition / dissolution during battery operation is prevented.

[0018] It is still another object of the present invention to provide a lithium ion secondary battery including the negative electrode.

[0019] Other objects and advantages of the present invention will become apparent from the following description and the accompanying drawings, in which: FIG. 1 is a block diagram of a method for manufacturing a semiconductor device according to the present invention; [Means for solving the problem]

[0020] The above object can be achieved by the features of the independent claims, and further embodiments can be explained by the features of the dependent claims and the detailed description of the invention.

[0021] A first aspect of the present invention relates to a negative electrode for a lithium secondary battery comprising a Li-M alloy containing lithium and a lanthanum group metal as a negative electrode active material.

[0022] According to a second aspect of the present invention, in the first aspect, the lanthanum group metal includes one or more selected from the group consisting of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu).

[0023] According to a third aspect of the present invention, in the first or second aspect, the lanthanum group metal includes lanthanum (La).

[0024] According to a fourth aspect of the present invention, in any one of the first to third aspects, the content of the lanthanum group metal is less than 15 wt% relative to 100 wt% of the Li-M alloy.

[0025] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the content of the lanthanum group metal is 1 wt% to 10 wt% relative to 100 wt% of the Li-M alloy.

[0026] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, the content of the lanthanum group metal is 1 mol or less relative to 100 wt % of the Li-M alloy.

[0027] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, the negative electrode is such that the Li-M alloy is composed of lithium (Li) and a lanthanum group metal (M).

[0028] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the Li-M alloy is 95 wt % or more in 100 wt % of the negative electrode active material.

[0029] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, the negative electrode includes a Li-M alloy in the form of a metal thin film as a negative electrode active material layer.

[0030] According to a tenth aspect of the present invention, in any one of the first to ninth aspects, the negative electrode further includes a current collector.

[0031] According to an eleventh aspect of the present invention, there is provided a lithium ion secondary battery including a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is according to any one of the aspects of the present invention.

[0032] According to a twelfth aspect of the present invention, in the eleventh aspect, the electrolyte comprises a mixture of an acyclic ether and a cyclic ether, and a volume ratio (v / v) of the acyclic ether to the cyclic ether in the mixture is 5:95 to 95:5.

[0033] According to a thirteenth aspect of the present invention, in the eleventh or twelfth aspect, the lithium secondary battery is a lithium-sulfur battery in which the positive electrode active material contains sulfur (S) or a sulfur (S) compound.

[0034] According to a fourteenth aspect of the present invention, in any one of the eleventh to thirteenth aspects, the lithium secondary battery has a coulombic efficiency of more than 90%.

[0035] According to a fifteenth aspect of the present invention, there is provided a method for producing a negative electrode for a lithium secondary battery according to any one of the first to tenth aspects, comprising the steps of: Melting metallic lithium to obtain a first melt; adding a lanthanum group metal to the obtained lithium melt to obtain a second melt; maintaining the second molten material at a temperature of 200° C. or more to alloy the second molten material; and cooling the second molten material obtained from the alloying step to obtain a lithium-lanthanum alloy.

[0036] According to a sixteenth aspect of the present invention, in the fifteenth aspect, the alloy is obtained in an ingot form, and the method further comprises the step of thinning the ingot into a plate-like structure of a predetermined thickness. Effect of the Invention

[0037] The lithium-lanthanum alloy negative electrode according to the present invention can be applied to the negative electrode of a lithium-sulfur battery. A lithium-sulfur battery incorporating the lithium-lanthanum alloy into the negative electrode has the effect of improving the life characteristics and coulombic efficiency. When the lithium-lanthanum alloy is used as the negative electrode, uniform electrochemical plating / elution of lithium is induced, and decomposition of LiPS and lithium salt due to interfacial side reactions can be effectively suppressed.

[0038] The following drawings attached to this specification are for illustrating preferred embodiments of the present invention, and serve to further understand the technical idea of ​​the present invention together with the detailed description of the invention, so the present invention should not be interpreted as being limited to only the matters described in the drawings. In addition, the shape, size, scale, ratio, etc. of the elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0039] [Figure 1] The cycle characteristics of the batteries manufactured in the examples and comparative examples are shown below. [Diagram 2] The coulombic efficiency of the batteries manufactured in the examples and comparative examples is shown. [Diagram 3] The coulombic efficiency of the batteries manufactured in the examples and comparative examples is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0040] The present invention will now be described in more detail.

[0041] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that corresponds to the technical concept of the present invention, based on the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention.

[0042] Unless otherwise limited, the detailed description defining or embodying the elements is applicable to all inventions and is not limited to the description of a particular invention, i.e., even if elements are disclosed individually in this specification, they may be considered to disclose an embodiment in which the elements are combined.

[0043] In addition, throughout the specification, when a part "comprises" a certain component, this does not mean excluding other components, but may further include other components, unless otherwise specified. The term "comprise" expressly includes the meaning of "consist of" and "essentially comprising", even if not expressly limited thereby.

[0044] As used herein, the term "essentially comprises" means "comprises at least 70%", preferably "comprises at least 80%", and most preferably "comprises at least 90%". When referring to the amounts of components of a mixture of substances, % means weight % relative to the total weight of each mixture, unless otherwise stated. For example, a material that essentially comprises polyethylene comprises polyethylene in an amount of 70% by weight or more, based on the total weight of the material.

[0045] As used throughout this specification, the terms "about," "substantially," and the like are used to mean a numerical value or a approximation thereof when given the inherent manufacturing and material tolerances in the stated sense, and are used to prevent unconscionable infringers from unfairly using disclosures in which precise or absolute numerical values ​​are recited to aid in the understanding of this application.

[0046] Throughout this specification, the phrase "A and / or B" means "A or B, or all of these."

[0047] In the present invention, the "specific surface area" is measured by the BET method, and specifically, can be calculated from the amount of nitrogen gas adsorbed at liquid nitrogen temperature (77K) using a BELSORP-mino II manufactured by BEL Japan.

[0048] As used herein, the term "polysulfide" refers to a polysulfide ion (S 2- , x=8, 6, 4, 2) and Lithium polysulfide (Li2S x or LiS x - , x=8, 6, 4, 2) is a concept that includes both.

[0049] The term "composite" as used herein means a material in which two or more materials are combined to form physically and chemically distinct phases, thereby exhibiting a more effective function.

[0050] The term "porosity" as used herein means the ratio of the volume of pores to the total volume of a structure, and the unit is "vol%" and may be used interchangeably with terms such as porosity and porosity. In the present invention, the measurement of the pores is not particularly limited, and may be measured, for example, by a BET (Brunauer-Emmett-Teller) method using nitrogen gas or a mercury porosimeter according to one embodiment of the present invention. In addition, the true density may be calculated from the density (apparent density) of the object to be measured, the composition ratio of the material contained in the object to be measured, and the density of each component, and the porosity of the electrode may be calculated from the difference between the apparent density and the true density (net density). For example, the porosity may be calculated according to the following formula 1.

[0051] formula 1 Porosity (volume%) = {1-(apparent density / true density)} x 100

[0052] The apparent density in the above formula 1 can be calculated from the following formula 2.

[0053] formula 2 Apparent density (g / cm 3 ) = (weight of object (g)) / {(thickness of object (cm)) × (area of ​​object (cm 2 ))}

[0054] Apparent density, or bulk density, is a measure of how much space a material occupies per unit volume, including the voids or air spaces contained within it. That is, apparent density includes the material in its solid state and the voids within its volume. Apparent density can be calculated by dividing the mass of a material by its total volume, which includes all the pores and air spaces within the material. The formula for calculating apparent density is:

[0055] (Formula) Apparent density = mass / total volume

[0056] The mass may be measured using a balance. For materials with regular patterns (e.g., regular cubes, cylinders, etc.), the dimensions may be measured using suitable tools such as tape measures or calipers, which are known methods in the art. For samples with irregular patterns, the volume may be measured by measuring the displacement of the liquid to determine a known change in volume, which may be the same as the volume of the material. Those skilled in the art will be able to apply other known methods to measure the volume and apparent density.

[0057] Net density (true density) refers to the density of a material without taking into account any voids or porosity contained therein. It is the mass of a solid material divided by its actual volume, excluding any void space in said volume. True density may be calculated by dividing the mass of a material by the solid, unoccupied volume of the material. The formula for calculating true density is:

[0058] (Formula) True density = mass / solid volume (void volume is not taken into account)

[0059] Unlike apparent density, true density does not take into account the total volume not including voids and indicates the intrinsic density of a material. True density can be determined by the methods described above or using the gas pycnometer method according to ISO 12154:2014 or other measurement methods known to those skilled in the art.

[0060] In the present invention, "particle size D 50 " means the particle size at 50% of the volume cumulative particle size distribution of the particles. 50 can be measured using a laser diffraction method. For example, after dispersing particles in a dispersion medium, the particles are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W to obtain a volume cumulative particle size distribution graph, and then the size of the particles that is 50% of the volume cumulative amount can be measured. Alternatively, in one embodiment of the present invention, the particle diameter D 50 can be measured according to ISO 9276. The size and thickness of each component in the drawings are arbitrarily shown for convenience of explanation, and the present invention is not limited to such illustration. In the drawings, thicknesses are enlarged to clearly show multiple layers and regions. In the drawings, thicknesses of some layers and regions are exaggerated for convenience of explanation.

[0061] negative electrode A first aspect of the present invention relates to a negative electrode active material for an electrochemical device and a negative electrode including the same.

[0062] The negative electrode includes an alloy (Li-M) containing a lanthanum group metal and lithium as a negative electrode active material. Preferably, the negative electrode includes an alloy of a lanthanum group metal and lithium as a negative electrode active material.

[0063] In one embodiment of the invention, the negative electrode comprises a Li-M alloy, where Li is lithium and M is a lanthanum group metal.

[0064] In one embodiment of the present invention, the alloy containing a lanthanum group metal and lithium may be stoichiometrically represented as xLi-yM, where x is the molar ratio of Li in the alloy, M is one or more, preferably one, selected from the lanthanum group metals, and y is the molar ratio of M in the alloy. In one embodiment of the present invention, x and y may each independently exceed 0. For example, x+y may be 0 or greater.

[0065] The lanthanum group metal M may include one or more, preferably one selected from the group consisting of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu). The metal M preferably includes lanthanum.

[0066] In one embodiment of the present invention, the content of the lanthanum group metal may be 1 mol% or less relative to the total content of the Li-M alloy (100 mol%). The content of the lanthanum group metal may be more than 0 mol% relative to the total content of the Li-M alloy (100 mol%). The content of the lanthanum group metal may be 0.01 mol% to 1 mol%, 0.05 mol% to 0.95 mol%, 0.1 mol% to 0.90 mol%, 0.15 mol% to 0.85 mol%, 0.20 mol% to 0.80 mol%, 0.25 mol% to 0.75 mol%, or 0.25 mol% to 0.6 mol% relative to the total content of the Li-M alloy (100 mol%).

[0067] In one embodiment of the present invention, the lithium content in the alloy may be 99 mol% or more relative to 100 mol% of the total amount of the Li-M alloy. The lanthanum group metal content may be less than 100 mol% relative to 100 mol% of the Li-M alloy. The lithium content may be in the range of 99 mol% to 99.99 mol%, 99.05 mol% to 99.95 mol%, 99.1 mol% to 99.9 mol%, 99.15 mol% to 99.85 mol%, 99.2 mol% to 99.8 mol%, 99.25 mol% to 99.75 mol%, or 99.4 mol% to 99.75 mol% relative to 100 mol% of the Li-M alloy.

[0068] The upper and / or lower limits of the metal M may be adjusted within an appropriate range in consideration of the electrochemical properties of the battery to which the final negative electrode is applied. When the negative electrode contains a Li-M alloy within the above range, the life characteristics and coulombic efficiency of the lithium secondary battery are improved. When the alloy contains an excessive amount of lanthanum group metal M, the coulombic efficiency may become unstable and the average efficiency value may be lower than that of a lithium metal negative electrode to which no alloy is applied.

[0069] In one embodiment of the present invention, the Li-M alloy may contain lanthanum group metal M in an amount exceeding 0 wt% based on 100 wt% of the total amount of the Li-M alloy. In one embodiment of the present invention, the Li-M alloy may contain lanthanum group metal M in an amount of 1 wt% or more based on 100 wt% of the total alloy. Meanwhile, the lanthanum group metal may be contained in an amount of less than 15 wt%. Meanwhile, in terms of improving life characteristics and coulombic efficiency, the lanthanum group metal M may be contained in the alloy in an amount of 3 wt% or more, 5 wt% or more, or 7 wt% or more. On the other hand, if an excessive amount of lanthanum group metal M is included in the alloy, the coulombic efficiency may become unstable and the average efficiency value may be lower than that of a lithium metal anode to which the alloy is not applied, so the amount may be controlled to be less than 15 wt%, 14 wt% or less, 13 wt% or less, 12 wt% or less, 11 wt% or less, 10 wt% or less, 7 wt% or less, 5 wt% or less, or 3 wt% or less. The weight percent (wt%) refers to the weight percent relative to 100 wt% of the total amount of the Li-M alloy. The upper and / or lower limits of the metal M may be controlled to an appropriate range in consideration of the electrochemical properties of the battery to which the anode is ultimately applied.

[0070] In one embodiment of the present invention, the Li-M alloy may contain 85 wt% or more and less than 100 wt% or 90 wt% or more and less than 100 wt% of lithium (Li) based on 100 wt% of the total weight of the Li-M alloy. In one embodiment of the present invention, the Li-M alloy may contain 85 wt% or more, 90 wt% or more, 93 wt% or more, or 95 wt% or more of lithium (Li) in the total alloy.

[0071] Meanwhile, according to one embodiment of the present invention, the weight ratio (wt%) of Li:metal M in the Li-metal M alloy may have a value of 99:1 to 85:15, 99:1 to 90:10, or 97:3 to 90:10, or 95:5 to 90:10, or 93:7 to 90:10, for example, 99:1 to 95:5 or 93:7 to 97:3.

[0072] In one embodiment of the present invention, the negative electrode may contain the Li-M alloy as a negative electrode active material in a range of 95 wt% or more, 95 wt% to 100 wt%, 98 wt% to 99.9 wt%, or 98 wt% to 99 wt%, for example, the negative electrode may be made of a Li-M alloy as a negative electrode active material.

[0073] Meanwhile, the negative electrode according to the present invention may be applied to a battery by preparing the Li-M alloy in a thin film form. That is, in the present invention, a Li-M alloy thin film may be used as the negative electrode active material layer. In one embodiment of the present invention, the thickness of the negative electrode active material layer may be 0.1 μm or more and 200 μm or less in terms of providing a sufficient lithium supply source for driving the battery and achieving high energy density. For example, the Li-M alloy thin film may have a thickness of 180 μm or less, or 160 μm or less, 150 μm or less, 140 μm or less, 130 μm or less, 120 μm or less, 110 μm or less, 100 μm or less, 80 μm or less, or 70 μm or less. Meanwhile, the thickness of the negative electrode active material layer may be 0.1 μm or more, 0.5 μm or more, 2 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, 50 μm or more, 70 μm or more, 75 μm or more, or 90 μm or more. The Li-M alloy thin film may have a thickness of 0.1 μm to 180 μm. In a specific embodiment of the present invention, the Li-M alloy thin film may have a thickness of 40 μm to 80 μm, or 50 μm to 70 μm. In one embodiment of the present invention, the negative electrode may be formed by the Li-M thin film alone without a current collector, or by bonding a current collector and a Li-M alloy thin film.

[0074] Thus, the negative electrode may be constructed of a Li-M alloy, with or without a current collector optionally included.

[0075] The thickness of the negative electrode can be measured using a known thickness measuring device when measuring the thickness of a battery element. For example, it can be measured using a contact type thickness measuring device such as a Mitutoyo handheld micrometer or a Stylus Profiler (Bruker, Dektak 150 Surface Profiler) or a rotary caliper (Maysun, RC-1W-200). For example, in the case of a stylus profiler, the measurement object is fixed to a sample stage so that the running direction of the tip and the surface of the measurement object are perpendicular, and the thickness can be measured by moving the stylus. In one embodiment, the stylus force is 5 mg and the measurement speed is 0.05 mm / s. Alternatively, in the present invention, the thickness of the negative electrode can be measured using a laser scan micrometer according to ASTM D374.

[0076] In one embodiment of the present invention, the Li-M alloy may be monolithic. The term "monolithic" means that there is no concentration gradient of the M metal in the Li-M alloy according to the present invention. Furthermore, the Li-M alloy according to the present invention may be substantially homogeneous throughout the alloy. The Li-M alloy according to the present invention may be homogeneous throughout the alloy. The Li-M alloy according to the present invention is a substantially homogeneous bulk material, where the entire bulk material is a continuous phase and homogeneous. That is, the M metal is all melted and the entire bulk is a continuous phase with lithium, and is in a substantially or completely homogeneous state.

[0077] In one embodiment of the present invention, the negative electrode current collector may be a negative electrode current collector commonly used in the art. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy may be used. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may have fine irregularities to enhance the binding force with the negative electrode active material. For example, the current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric. For example, when a metal thin film type current collector is used, the current collector may have a thickness of 1 μm to 20 μm.

[0078] Meanwhile, the method for forming the Li-M thin film is not particularly limited, and any method for forming a layer or film commonly used in the art, such as a compression method or a coating method, may be used.

[0079] The Li-M thin film includes the steps of: a) melting metallic lithium to obtain a lithium melt (first melt), b) adding metal M to the lithium melt obtained in step a) to obtain a lithium-M metal melt (second melt), c) maintaining the lithium-M metal melt obtained in step b) at a temperature of 200° C. or higher, d) cooling the lithium-M metal melt obtained in step c) to obtain a lithium-M metal ingot, and e) producing a lithium-M metal alloy thin film from the lithium-M metal alloy ingot. In step c), lithium and M metal may be alloyed.

[0080] The method may include placing a solid piece of lithium, such as a lithium ingot, together with a solid piece of M metal pellets in a suitable heating means (e.g., a vessel). The heating means may further include a stirring means for stirring the bimetallic melt and a means for providing an inert gas atmosphere to the heating means. The step a) of providing metallic lithium and M metal may not include a sputtering step, such as DC sputtering. Rather, the melting in step b) may include stirring the melt. The approach is more cost effective in providing a lithium-M metal alloy foil with a much more homogeneous and improved distribution of the M metal.

[0081] The melting may involve heating metallic lithium together with metal M at a temperature between 200°C and 500°C.

[0082] The cooling in step d) may be to room temperature.

[0083] In one embodiment of the present invention, the method for producing the lithium-metal M thin film may include a method of roll-pressing a lithium-metal M alloy ingot to obtain a lithium-metal M thin film. In the roll-pressing, heat and pressure may be applied simultaneously, and may be performed using a hot roll press or the like.

[0084] Meanwhile, in one embodiment of the present invention, the method for preparing an electrode according to the present invention may further include the following step f) of bonding / adhering the lithium-metal M thin film obtained above to a current collector.

[0085] secondary battery A second aspect of the present invention relates to a lithium ion secondary battery including the negative electrode.

[0086] Positive electrode (lithium-sulfur battery) The lithium ion secondary battery may be a lithium-sulfur battery.

[0087] The positive electrode according to the present invention includes a current collector and a positive electrode active material layer disposed on at least one surface of the current collector.

[0088] The current collector can be any one used in the art, as long as it has electrical conductivity and is used as a current collector component. For example, the positive electrode current collector can be stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector usually has a thickness of 3 μm to 500 μm, and it is also possible to form fine irregularities on the surface of the positive electrode current collector to increase the adhesive force of the positive electrode active material. The positive electrode current collector can be used in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0089] In one embodiment of the present invention, the positive electrode active material layer includes a positive electrode active material, a conductive material, and a binder material, and may include 80 wt% to 97 wt% of the positive electrode active material, 2 wt% to 10 wt% of the conductive material, and 2 wt% to 10 wt% of the binder, based on the total weight of the positive electrode active material, the conductive material, and the binder material.

[0090] In the present invention, the positive electrode active material includes a sulfur-carbon composite. Preferably, the positive electrode active material includes 80 wt% or more, preferably 90 wt% or more of the sulfur-carbon composite relative to 100 wt% of the positive electrode active material, and more preferably, the positive electrode active material may be composed of only the sulfur-carbon composite. Also, the sulfur content is preferably 70 wt% or more relative to 100 wt% of the sulfur-carbon composite.

[0091] In one embodiment of the present invention, the sulfur-carbon composite may be a composite of the sulfur and the carbon material, or may be a coating or support having a core-shell structure. The core-shell coating may be a coating of either sulfur or the carbon material on the other material, for example, the surface of the carbon material may be surrounded by sulfur, or vice versa. The carbon material may have a porous structure having pores inside and on the surface of the body, and in particular, the internal pores may be filled with sulfur. The sulfur-carbon composite may be in any form as long as it satisfies the content ratio of the sulfur-based compound and the carbon material described below, and is not limited to the present invention. Meanwhile, in the present invention, the content of sulfur is preferably 70 wt % or more based on the total weight of the positive electrode active material.

[0092] The sulfur alone does not have electrical conductivity, and therefore is used in combination with a carbon material.

[0093] In one embodiment of the present invention, the sulfur is inorganic sulfur (S8), Li2S n (n≧1), disulfide compounds such as 2,5-dimercapto-1,3,4-thiadiazole, 1,3,5-trithiocyanuric acid, etc., organic compounds and carbon-sulfur polymers (C2S x ) n , x=2.5 to 50, n≧2). Preferably, inorganic sulfur (S8) may be included.

[0094] The carbon material has a porous structure including a plurality of pores on the surface and inside, and serves as a support that provides a framework for uniform and stable immobilization of sulfur, and compensates for the low electrical conductivity of sulfur to facilitate electrochemical reactions. In particular, the carbon material that serves as a sulfur support in the sulfur-carbon composite has a wide BET specific surface area and an appropriate particle size D 50When the catalyst has a certain size, it is possible to increase the amount of sulfur supported, but at the same time, the irreversible capacity is low, and the energy density is increased, thereby increasing the utilization rate of sulfur during an electrochemical reaction.

[0095] In one embodiment of the present invention, the BET specific surface area of ​​the carbon material is at least 100 m 2 / g or more, up to 3,000m 2 In addition, or independently, the carbon material may have a primary particle diameter D 50 can be from 1 μm to 50 μm.

[0096] The BET specific surface area and particle size D of the carbon material 50 When the range is satisfied, sulfur can be uniformly dispersed on the inside and outside surfaces of the carbon material, while the irreversible capacity can be reduced and the electrochemical reactivity of sulfur can be increased. In addition, the use of the carbon material improves the electrochemical reactivity, stability, and electrical conductivity of the sulfur-carbon composite, thereby improving the capacity and life characteristics of the lithium-sulfur battery and showing optimal charge / discharge performance even if sulfur loss or volume change occurs during charge / discharge.

[0097] The particle diameter D of the primary particles 50 If the diameter of the primary particles is more than 50 μm, it is difficult for the lithium ions to move into the particles due to the limitations of mass transport, making it difficult to efficiently use the sulfur located in the center of the carbon. 50 If the particle size is less than 1 μm, it is difficult to increase the solid content because a large amount of solvent is required in the process of producing the electrode slurry, and sufficient pores between the particles are not secured, resulting in a decrease in output.

[0098] In the sulfur-carbon composite of the present invention, the carbon material used as the sulfur support can be generally prepared by carbonizing various carbon precursors.

[0099] Meanwhile, in one embodiment of the present invention, the pores of the carbon material may have a diameter of 0.5 nm to 200 nm based on the longest diameter. The carbon material is not particularly limited as long as it is spherical, rod-like, needle-like, plate-like, tubular or bulk-like and can be generally used in lithium-sulfur batteries.

[0100] The carbon material may be any porous and conductive carbon-based material commonly used in the art, and may include at least one selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), graphite such as natural graphite, artificial graphite, and expanded graphite, carbon nanoribbons, carbon nanobelts, carbon nanorods, and activated carbon.

[0101] In the sulfur-carbon composite according to the present invention, the sulfur is located on at least one of the inside and outside surfaces of the pores of the carbon material, and in this case, it may be present in an area of ​​less than 100%, preferably 1% to 95%, more preferably 60% to 90% of the entire inside and outside surface of the carbon material. When the sulfur is present on the surface of the carbon material within the above range, it can exhibit the maximum effect in terms of the electron transfer area and the wettability of the electrolyte. Specifically, since the sulfur is impregnated thinly and uniformly on the surface of the carbon material in the above range, it is possible to increase the electron transfer contact area during the charge and discharge process. If the sulfur is located in an area of ​​100% of the entire surface of the carbon material, the carbon material is completely covered with sulfur, which reduces the wettability of the electrolyte and the contact with the conductive material contained in the electrode, making it difficult to transfer electrons and unable to participate in the reaction.

[0102] In one embodiment of the present invention, the sulfur-carbon composite can be obtained by the following production method.

[0103] The method for producing the sulfur-carbon composite according to the present invention is not particularly limited and may be a method commonly known in the art, and may be prepared by a composite method including a step of (S1) mixing a carbon material with sulfur and a step of (S2) composite.

[0104] The mixing in step (S1) is for increasing the degree of mixing of sulfur and the carbon material, and may be performed using a stirrer commonly used in the art. In this case, the mixing time and speed may be selectively adjusted according to the content and conditions of the raw materials.

[0105] The compounding method in step (S2) is not particularly limited in the present invention, and may be a method commonly used in the art. For example, a method commonly used in the art, such as dry compounding or wet compounding such as spray coating, may be used. For example, a method may be used in which the mixture of sulfur and carbon material obtained after mixing is heat-treated so that the molten sulfur is uniformly coated on the inside and outside surfaces of the carbon material. Meanwhile, in one embodiment of the present invention, a process of pulverizing the mixture of sulfur and carbon material by a method such as ball mill pulverization is performed before the heat treatment. In one embodiment of the present invention, the heat treatment is performed at a temperature condition of 120° C. to 160° C. for about 20 minutes to 24 hours, and a heating device such as an oven may be used.

[0106] The sulfur-carbon composite prepared by the above-mentioned preparation method has a structure with a high specific surface area, a high sulfur loading, and an improved sulfur utilization rate. This not only improves the electrochemical reactivity of sulfur, but also improves the accessibility and contactability of the electrolyte, thereby improving the capacity and life characteristics of lithium-sulfur batteries.

[0107] Other cathode materials In one embodiment of the present invention, the positive electrode active material may be composed only of the sulfur-carbon composite, or may further include one or more additives selected from a transition metal element, a Group IIIA element, a Group IVA element, sulfur compounds of these elements, and alloys of these elements with sulfur.

[0108] In a specific embodiment of the present invention, the positive electrode active material layer may include a lithium transition metal composite oxide represented by the following Chemical Formula 1:

[0109] [Chemical formula 1] Li a Ni b Co c M 1 d M 2 e O2

[0110] In the above Chemical Formula 1, M 1 is Mn, Al or a combination thereof, and desirably may be Mn or Mn and Al.

[0111] Said M 2 is at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb, preferably at least one selected from the group consisting of Zr, Y, Mg and Ti, more preferably Zr, Y or a combination thereof. 2 Although the elements are not essential, when contained in an appropriate amount, they can play a role in promoting grain growth during firing or improving the stability of the crystal structure.

[0112] Conductive material The conductive material is used to impart conductivity to the negative electrode, and can be used without any particular limitation as long as it has conductivity without inducing a chemical change in the battery to be constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotube, and other carbon-based materials; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be usually contained in an amount of 1 wt% to 30 wt%, preferably 1 wt% to 20 wt%, more preferably 1 wt% to 10 wt% based on the total weight of the negative electrode active material layer.

[0113] In one embodiment of the present invention, the content of the binder may be 1 to 10 wt % based on the total weight of the positive electrode active material layer. If the content of the binder is less than this range, the physical properties of the positive electrode may deteriorate and the positive electrode active material and the conductive material may separate. If the content of the binder exceeds this range, the relative proportion of the positive electrode active material and the conductive material in the positive electrode may decrease, thereby decreasing the battery capacity. Therefore, it is preferable to determine an appropriate content within this range.

[0114] Binder Material The binder material serves to improve the adhesion between positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples of the binder material include polyvinyllidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof. One or a mixture of two or more of these may be used.

[0115] electrode assembly Yet another aspect of the present invention relates to an electrode assembly including the negative electrode. The negative electrode may be as described above. The positive electrode may include the sulfur-carbon composite as a positive electrode active material. The electrode assembly includes a negative electrode, a positive electrode, and a separator interposed between the negative electrode and the positive electrode. For example, the separator may be interposed between the negative electrode and the positive electrode and stacked to form a stacked or stacked / folded type structure, or may be wound to form a jelly roll type structure. In addition, when a jelly roll structure is formed, a separator may be further disposed on the outside to prevent contact between the negative electrode and the positive electrode.

[0116] separation membrane The separator is disposed in the electrode assembly in a manner interposed between the negative electrode and the positive electrode. The separator can be any separator that is commonly used as a separator in a lithium secondary battery by separating the negative electrode and the positive electrode and providing a passage for lithium ions to move. Specifically, the separator may be a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof. In addition, a typical porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, a separator coated with a coating layer containing a ceramic component or a polymer material may be used to ensure heat resistance or mechanical strength.

[0117] battery Yet another aspect of the present invention relates to an electrochemical device including the electrode assembly. The electrochemical device includes a battery case in which an electrode assembly and an electrolyte are housed together, and the battery case may be of any suitable type, such as a pouch type or a metal can type, that is commonly used in the art. The shape of the battery is not particularly limited, and may be of various shapes, such as a cylindrical shape, a stacked type, or a coin type.

[0118] electrolyte In the present invention, the electrolyte may include an organic solvent and a lithium salt.

[0119] The electrolyte may be an electrolytic solution containing a lithium salt and a non-aqueous solvent that serves as a medium for the migration of ions involved in the electrochemical reaction of the lithium secondary battery.

[0120] In the present invention, the non-aqueous solvent may be an electrolyte solution containing a mixture of an acyclic ether and a cyclic ether.

[0121] In the present invention, the electrolyte may be an electrolytic solution in which the volume ratio of acyclic ether to cyclic ether is 5:95 to 95:5 (v / v).

[0122] In the present invention, the volume ratio (v / v) of the acyclic ether to the cyclic ether may be 5:95 to 95:5 (v / v). Specifically, it may be 80:20 to 20:80, more specifically 70:30 to 30:70, 60:40 to 40:60, for example, 50:50. In this specification, the volume ratio is the ratio of "volume % of non-cyclic ether" to "volume % of cyclic ether" in a mixture of the acyclic ether and the cyclic ether.

[0123] For example, in a specific embodiment of the present invention, the volume ratio (v / v) of the acyclic ether to the cyclic ether may be 50:50 (v / v).

[0124] For example, in a specific embodiment of the present invention, the volume ratio (v / v) of 1,3-dioxolane to dimethyl ether may be 5:95 to 95:5 (v / v).

[0125] Organic solvents The organic solvent is a solvent for the electrolyte and serves as a medium that allows the movement of ions involved in the electrochemical reaction of the battery. As the organic solvent, any organic solvent that is commonly used in lithium secondary battery electrolytes may be used without limitation. For example, ethers, esters, amides, linear carbonates, cyclic carbonates, etc. may be used alone or in combination of two or more. Among these, ether-based compounds may be used as a representative example.

[0126] The ether-based compounds may include acyclic ethers and cyclic ethers.

[0127] For example, the acyclic ether may be at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, dimethoxyethane, ditrimethoxymethane, diethoxyethane, dimethoxypropane, ethylene glycol ethyl methyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethylene ether, butylene glycol ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.

[0128] For example, the cyclic ethers include methylfuran, 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene, and isosorbide dimethyl ether. The thiophene may be at least one selected from the group consisting of, but is not limited to, furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene.

[0129] Examples of the ester of the organic solvent include, but are not limited to, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, ε-caprolactone, and mixtures of two or more thereof.

[0130] Specific examples of the linear carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more thereof.

[0131] Specific examples of the cyclic carbonate compound include ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof, or mixtures of two or more thereof. Examples of such halides include, but are not limited to, fluoroethylene carbonate (FEC).

[0132] Lithium salt The lithium salt is a compound capable of providing lithium ions in an electrolyte. Examples of such lithium salts include LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3CO2, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiCH3SO3, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiC4BO8, LiCl, LiBr, LiB 10 Cl 10 , LiI or LiB(C2O4)2 may be used. In the present invention, in order to increase the utilization possibility of sulfur and realize a high capacity and high voltage battery, it is preferable that the lithium salt includes Li-TFSI. More preferably, the lithium salt may include LiN(CF3SO2)2(Li-TFSI) in an amount of 80wt% or more, 90wt% or more, or 100% based on 100wt% of the total lithium salt.

[0133] The concentration of the lithium salt is in the range of 0.1M to 2.0M, preferably 0.5M to 1M, more preferably 0.5 to 0.75M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can be effectively moved. When the concentration of the lithium salt is below the above range, it is difficult to ensure ion conductivity suitable for battery operation, and when the concentration of the lithium salt is above the above range, the viscosity of the electrolyte increases, so that the mobility of lithium ions decreases, or the decomposition reaction of the lithium salt itself increases, so that the performance of the battery may decrease.

[0134] In one specific embodiment of the present invention, in an electrolyte including a first solvent, a second solvent, and a lithium salt, the molar ratio of the lithium salt to the second solvent to the first solvent may be 1:0.5-3:4.1-15. In addition, in one embodiment of the present invention, the molar ratio of the lithium salt to the second solvent to the first solvent may be 1:2:4-13, or 1:3:3-10, or 1:4:5-10, and the electrolyte included in the lithium-sulfur battery of the present invention may include a first solvent including a fluorine-based ether compound at a higher content ratio than the second solvent including a glyme-based compound.

[0135] Other additives In addition to the electrolyte components, the electrolyte may further contain additives for the purpose of improving the life characteristics of the battery, suppressing the capacity reduction of the battery, improving the discharge capacity of the battery, etc. For example, the additives may be nitric acid compounds, nitrous acid compounds, haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc., which may be used alone or in combination. The additive may be included in an amount of 0.1 wt% to 10 wt%, preferably 0.1 wt% to 5 wt%, or 0.5 wt% to 4 wt%, 0.7 wt% to 3 wt%, 0.9 wt% to 2 wt%, or 0.95 wt% to 1.5 wt%, based on the total weight of the electrolyte.

[0136] In a specific embodiment of the present invention, the electrolyte may include a nitrate compound and / or a nitrite compound as an additive. The nitrate compound / nitrite compound forms a stable coating on the lithium metal electrode, which is the negative electrode, and thus improves charge / discharge efficiency. The nitric acid or nitrite-based compound may include, but is not limited to, one or more selected from the group consisting of inorganic nitric acid or nitrite compounds such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), and ammonium nitrite (NH4NO2); organic nitric acid or nitrite compounds such as methyl nitrate, dialkylimidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrate, propyl nitrate, butyl nitrate, pentyl nitrate, and octyl nitrate; and organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, and dinitrotoluene, and combinations thereof. In a preferred embodiment of the present invention, the additive may include lithium nitrate.

[0137] In one embodiment of the present invention, the average coulombic efficiency of the lithium secondary battery is 90% or more, or 95% or more, or 98% or more. The coulombic efficiency means a percentage ratio of discharge capacity to charge capacity. The coulombic efficiency of the battery may be measured at 25° C. with 0.2 C charge / 0.3 C discharge. The average coulombic efficiency may be calculated from an average of 100 to 200 cycles, for example, 150 cycles, of the battery. Also, one cycle may be from SOC (state of charge) 100 to SOC 0. Therefore, the average coulombic efficiency may be measured at 25° C. with 0.2 C charge / 0.3 C discharge for 150 cycles. Meanwhile, in a specific embodiment of the present invention, the charge capacity (mAh) and the discharge capacity (mAh) may be measured using a charger / discharger manufactured by WONIK PNE CO., LTD. The measurement conditions may be, for example, a range of 1.8 V to 2.5 V (vs. Li / Li+), a charge of 0.1 C to 0.5 C, and a discharge of 0.1 C to 0.5 C.

[0138] In a specific embodiment of the present invention, the battery for which the average coulombic efficiency is measured may be manufactured by stacking a total of seven positive electrodes and eight negative electrodes with separators sandwiched therebetween.

[0139] The present invention also provides a battery module including the lithium-sulfur battery as a unit cell, which can be used as a power source for medium to large devices that require high temperature stability, long cycle characteristics, and high capacity characteristics.

[0140] Examples of the medium- to large-sized devices include, but are not limited to, power tools powered by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (Escooters); electric golf carts; and power systems.

[0141] Hereinafter, preferred embodiments of the present invention will be described to aid in understanding the present invention. However, the following embodiments are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various modifications and alterations are possible within the scope of the scope and technical ideas of the present invention. Of course, such modifications and alterations are included in the scope of the appended claims.

[0142] Working Example Anode manufacturing Li metal was put into a heating furnace and melted by applying heat at a temperature of 200°C to 500°C. Metal M pellets were then put into the furnace in the ratio shown in Table 1 below and melted. The furnace was then maintained at 200°C to 500°C and stirred. The resultant was cooled to form a Li-M alloy ingot. The ingot was extruded and rolled to a thickness of 60 μm.

[0143] [Table 1]

[0144] Battery manufacturing Carbon nanotubes and sulfur were uniformly mixed (sulfur:carbon nanotubes = 75wt%:25wt%) and placed in an oven at 155°C for 30 minutes to prepare a sulfur-carbon composite. The sulfur content in the 100wt% sulfur-carbon composite was 75wt%. 96wt% of the prepared sulfur-carbon composite and 4wt% of styrene butadiene rubber / carboxymethyl cellulose (SBR / CMC, 7:3 weight ratio) as a binder were mixed to prepare a slurry for preparing a positive electrode. The solid content in the slurry was 25wt%. The slurry was applied to both sides of an aluminum current collector with a thickness of 20μm, dried at 50°C for 12 hours, and pressed using a roll press to prepare a positive electrode. The load of the positive electrode active material was 4.00mAh / cm 2The porosity of the positive electrode active material was 72 vol%. The porosity was calculated from the true density d of the positive electrode active material layer, the volume (apparent volume) v of the positive electrode active material, and the mass m of the positive electrode active material layer, as follows: Porosity (%) = {1-m / (vd)} x 100.

[0145] The electrolyte used was a mixture of 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt% lithium nitrate (LiNO3) dissolved in an organic solvent consisting of 1,3-dioxolane and dimethyl ether (DOL:DME = 1:1 (volume ratio)).

[0146] The prepared positive and negative electrodes were placed facing each other, and a polyethylene porous film with a thickness of 16 μm and a porosity of 68 vol% was placed between them as a separator, and then the resultant was placed in a pouch, and the prepared electrolyte was injected and sealed to prepare a lithium-sulfur battery. The battery was constructed by stacking and folding a total of seven positive electrodes and eight negative electrodes with the separator sandwiched between them. The prepared battery was charged at 0.2 C and discharged at 0.3 C at 25° C. to confirm the cycle characteristics and efficiency.

[0147] Evaluation results FIG. 1 shows the cycle characteristics of the batteries manufactured in the Examples and Comparative Examples. It was confirmed that the batteries of Examples 1 and 2 had better cycle characteristics than the battery of Comparative Example 1. In particular, Example 2, in which the ratio of lanthanum in the negative electrode was 10 wt % by weight, showed better cycle characteristics than Example 1. Meanwhile, Comparative Example 2, similar to Comparative Example 1, showed no improvement in cycle characteristics. Also, Comparative Example 4, similar to Comparative Example 1, showed no improvement in cycle characteristics.

[0148] 2 and 3 show the Coulombic efficiency of the batteries manufactured in the Examples and Comparative Examples. As seen from these, it was confirmed that the average Coulombic efficiency of the batteries of Examples 1 and 2 was increased compared to the battery of Comparative Example 1. In particular, it was confirmed that the battery of Example 2 (10 wt% La) realized a higher average efficiency value than the battery of Example 1 (5 wt% La). Furthermore, as a result of examining the battery of Comparative Example 3, it was confirmed that when lanthanum was applied at 15 wt% or more, the Coulombic efficiency was very unstable and the average efficiency value was also lower than that of the battery of Comparative Example 1.

Claims

1. A negative electrode for a lithium secondary battery comprising a Li-M alloy containing lithium (Li) and a lanthanum group metal (M).

2. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the lanthanum group metal comprises at least one selected from the group consisting of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu).

3. 3. The negative electrode for a lithium secondary battery according to claim 2, wherein the lanthanum group metal comprises lanthanum (La).

4. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the content of the lanthanum group metal is less than 15 wt % relative to 100 wt % of the Li-M alloy.

5. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the content of the lanthanum group metal is 1 wt % or more and 10 wt % or less, based on 100 wt % of the Li-M alloy.

6. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the Li-M alloy is composed of lithium (Li) and a lanthanum group metal (M).

7. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode contains 95 wt % or more of the Li-M alloy in 100 wt % of a negative electrode active material.

8. 2. The negative electrode of claim 1, wherein the negative electrode comprises a Li-M alloy in the form of a metal thin film as a negative electrode active material layer.

9. 9. The negative electrode for a lithium secondary battery according to claim 8, wherein the negative electrode further comprises a current collector.

10. A lithium secondary battery comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is the one according to any one of claims 1 to 9.

11. The lithium secondary battery according to claim 10, wherein the electrolyte is an electrolytic solution containing a mixture of a cyclic ether and an acyclic ether, and the acyclic ether and the cyclic ether are contained in the electrolytic solution in a volume ratio of 5:95 to 95:

5.

12. The lithium secondary battery according to claim 10, wherein the lithium secondary battery is a lithium-sulfur battery in which a positive electrode active material contains sulfur (S) or a sulfur (S) compound.

13. 11. The lithium ion secondary battery of claim 10, wherein the lithium secondary battery has an average coulombic efficiency of greater than 90%.

14. A method for producing a negative electrode for a lithium secondary battery according to any one of claims 1 to 9, comprising the steps of: Melting metallic lithium to obtain a first melt; adding a lanthanum group metal to the first melt to obtain a second melt; maintaining the second molten material at a temperature of 200° C. or more to alloy the second molten material; and cooling the second molten material obtained in the alloying step to obtain a lithium-lanthanum alloy.

15. The method for manufacturing a negative electrode for a lithium secondary battery according to claim 14, further comprising the step of obtaining the alloy in an ingot form and thinning the ingot into a plate-like structure having a predetermined thickness.

Citation Information

Patent Citations

  • Lanthanum lithium aluminum alloy

    CN106816578A

  • Lithium secondary battery

    JP1996083606A

  • Method for manufacturing a lithium metal electrode, a lithium metal electrode manufactured by the method, and a lithium secondary battery including the same

    JP2023533051A

  • Negative electrode and method for production thereof, and non-aqueous electrolyte secondary battery

    WO2010041399A1

  • Method for manufacturing lithium metal electrode, lithium metal electrode manufactured thereby, and lithium secondary battery comprising same

    WO2022060021A1